PERAN KEPEMIMPINAN KEPALA SEKOLAH DALAM MEMBANGUN BUDAYA SEKOLAH YANG EFEKTIF SEBAGAI UPAYA MEWUJUDKAN KEBERHASILAN MANAJEMEN BERBASIS SEKOLAH DI SD NO. 2 ABIANBASE - Chindytia Chindytia; Ida Bagus Gede Surya Abadi; Ni Luh Rita Wulandari; Ni Putu Tika Widaputri; Ni Komang Nandini (STKIP Pesisir Selatan, 2026)
This study aims to analyze the principal's leadership role in building an effective school culture as an effort to achieve successful School-Based Management at SD No. 2 Abianbase. This research used a qualitative method with a case study approach. Data were obtained through interviews, observation, and documentation, then analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results indicate that the principal plays a strategic role through visionary leadership in designing the direction of school development, participatory leadership in involving the school community in decision-making, and collaborative leadership in building partnerships with parents, the school committee, and the surrounding community. These leadership practices impact the formation of a positive, open, adaptive school culture oriented toward continuous improvement of educational quality, thereby strengthening the implementation of School-Based Management. The novelty of this study lies in the integration of visionary, participatory, and collaborative leadership as the main foundations in establishing an effective school culture that supports the success of participatory and sustainable elementary school management.